IoT 기반 서비스를 위한 데이터 처리 미들웨어와 관리시스템 설계 및 구현 - 이연식(Yon-Sik Lee); 문영채(Young-Chae Mun) (한국컴퓨터정보학회논문지, 2019)
Sensor application systems for remote monitoring and control are required, such as the establishment of databases and IoT service servers, to process data being transmitted and received through radio communication modules, controllers and gateways. This paper designs and implements database server, IoT service server, data processing middleware and IoT management system for IoT based services based on the controllers, communication modules and gateway middleware platform developed. For this, we firstly define the specification of the data packet and control code for the information classification of the sensor application system, and also design and implement the database as a separate server for data protection and efficient management. In addition, we design and implement the IoT management system so that functions such as status information verification, control and modification of operating environment information of remote sensor application systems are carried out. The implemented system can lead to efficient operation and reduced management costs of sensor application systems through site status analysis, setting operational information, and remote control and management. KCI Citation Count: 0